PENGEMBANGAN MEDIA PUZZLE PADA MATERI SUHU DAN KALOR IPA SD - Iis Sri Sugiarti; Setiyani .; Dian Permana Putri (Jurnal Pesona Dasar, 2020)
This study aims to determine the results of valid puzzle media development and the feasibility of developing practical puzzle media on temperature and heat material. In this study, the authors chose a puzzle with Microsoft PowerPoint as a tool to develop a medium. This research uses descriptive qualitative data analysis. With the Thiagarajan 4D model, namely defining, designing, and developing this research only goes through 3 stages up to the develop stage. The instrument used was a validation sheet which was analyzed using a Likert scale. Data collection techniques are observation, material and media expert validation sheets and teacher practicality sheets. The results showed that according to the expert the material was in a very valid category with a good predicate of 95.8% with improvement results. It's worth using. The validation result according to media experts is 90% with a good predicate is very valid, while the practicality or teacher response is 77.5% with a good predicate very feasible.